2018
DOI: 10.3889/oamjms.2018.337
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Vitamin C Intake on Muscle Damage in Male Adolescents Performing Strenuous Physical Activity

Abstract: BACKGROUND:Strenuous non-regular exercise increases reactive oxygen species ROS level leading to an impaired balance between the endogenous antioxidant defence system and the free radicals production. Antioxidants intake can detoxify the peroxides produced during exercise, attenuating the inflammatory responses and therefore may prevent exercise-induced muscle damage.AIM:The purpose of this study was to determine the role of vitamin C intake in attenuating markers of muscle damage, oxidative stress and inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The additional nutrients (two kiwifruits) in the intake group were energy 96 kcal, vitamin C 261 mg and Vitamin E 2.3 mg per day. It was reported that intake of 500 mg vitamin C inhibits lipid peroxidation [ 7 ]. Muscle damage markers of CK and LDH reduces by inhibiting lipid peroxidation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The additional nutrients (two kiwifruits) in the intake group were energy 96 kcal, vitamin C 261 mg and Vitamin E 2.3 mg per day. It was reported that intake of 500 mg vitamin C inhibits lipid peroxidation [ 7 ]. Muscle damage markers of CK and LDH reduces by inhibiting lipid peroxidation [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that intake of 500 mg vitamin C inhibits lipid peroxidation [ 7 ]. Muscle damage markers of CK and LDH reduces by inhibiting lipid peroxidation [ 7 ]. Moreover, it was reported that oxidative activity was not promoted by low dose intake (vitamin A 400 µg, vitamin E 15 mg and vitamin C 30 mg) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For three months, they were also given 500 mg of vitamin C each day. Vitamin C decreased exercise-induced muscle damage and oxidative stress, according to the study [68]. Evans and colleagues investigated untrained individuals' muscle force and athletic performance in a research study.…”
Section: Enhancement Of Endogenous Antioxidant Defense Mechanisms Against Exercise-induced Oxidative Stress (Os)mentioning
confidence: 99%
“…L-ascorbic acid) and vitamin E (α-tocopherol) are two essential micronutrients, with redoxdependent and independent biochemical functionality (Owens et al, 2019). Several studies have investigated the effects on EIMD indices and save few exceptions (Gabrial et al 2018;Righi et al, 2020), the general consensus is that both vitamins show limited ability to positively impact the signs and symptoms of EIMD (Thompson et al 2001;Thompson et al 2004;Shafat et al, 2004;McGinley et al, 2009;Sousa et al, 2014;Candia-Luján et al, 2014;de Oliveira et al 2019;Owens et al 2019). Gabrial et al (2018) examined the role of vitamin C intake in attenuating markers of muscle damage, oxidative stress and inflammatory responses in 20 recreationally active males that were regularly involved (2-3 times per week) in strenuous recreational exercise.…”
Section: Vitamin C and Vitamin Ementioning
confidence: 99%